2009
DOI: 10.1002/bdra.20589
|View full text |Cite
|
Sign up to set email alerts
|

Normal and abnormal anatomy of the cerebellar vermis in midgestational human fetuses

Abstract: Prenatal ultrasound images that suggest moderate-to-severe hypoplasia of the cerebellar vermis may reflect relatively subtle malformations, which are recognized histologically by direct comparison with stage-matched control data. The data in this series and others suggest a somewhat consistent pattern of lobular malformation, which affects the caudal cerebellum, particularly the nodulus, most severely. Rotation of the cerebellum, secondary to an enlarged fourth ventricle, may account for discordance between ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…The recent study by Kapur et al 16 has shed more light on the discrepancy between a lack of visualization of the vermis on sonography and postmortem findings. In particular, their study verifies our finding that even in severe cases of Dandy‐Walker malformations, the vermian biometric parameters may be preserved until later stages of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent study by Kapur et al 16 has shed more light on the discrepancy between a lack of visualization of the vermis on sonography and postmortem findings. In particular, their study verifies our finding that even in severe cases of Dandy‐Walker malformations, the vermian biometric parameters may be preserved until later stages of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Although knowledge of the true size of the fetal vermis is paramount in the evaluation of posterior fossa abnormalities, the literature reports few data that compare normal and abnormal vermian biometric parameters 14 , 15 . Kapur et al 16 attempted to correlate fetal vermian biometric parameters with histopathologic findings in healthy midgestation fetuses and 3 fetuses with an abnormal posterior fossa. Paladini and Volpe 14 used a small number of control fetuses and evaluated only the vermian height, which may be normal in cases of vermian rotation 4 .…”
mentioning
confidence: 99%
“…In recent years, several excellent studies of foetuses with cerebellar malformations have been published with meticulous observations including various immunocytochemical neuronal and glial cell markers [25,26,27,28,29]. A few of these studies employed synaptophysin but interpretation was limited by a lack of published control data, so that reactivity was noted as either present or absent without relation to expected maturational pattern and no substantive conclusions could be drawn from these observations [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…A few of these studies employed synaptophysin but interpretation was limited by a lack of published control data, so that reactivity was noted as either present or absent without relation to expected maturational pattern and no substantive conclusions could be drawn from these observations [23,25]. Other studies providing original, useful data with other immunocytochemical cell markers, and with genetic correlation, did not employ synaptophysin as a tissue marker for the same reason of lack of control studies for interpretation [27,28,29]. Nakamura et al [30], by contrast, demonstrated intense synaptophysin immunoreactivity around Purkinje neurons in hereditary cerebellar cortical atrophy in an adult male, which they interpreted as an abnormal increase in presynaptic terminals to compensate for loss of synapses on Purkinje cells that had degenerated or disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation